2019
DOI: 10.1177/0170840619868268
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Orchestration in Multi-stakeholder Innovation Networks: Practices of mobilizing multiple, diverse stakeholders across organizational boundaries

Abstract: The prominence of inter-organizational networks for innovation raises questions about how to support collaboration between multiple, diverse stakeholders. We focus on network orchestration and examine the practices that support orchestrators in dealing with the challenges brought by the number and diversity of stakeholders. Using qualitative, longitudinal data from an innovation network of 57 stakeholders, we identify three types of orchestration practices – connecting, facilitating and governing – and observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
123
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 121 publications
(183 citation statements)
references
References 58 publications
4
123
0
7
Order By: Relevance
“…Existing studies on network orchestration focused on one type of orchestrator at a time (e.g. UK government organization in Paquin and Howard-Grenville, 2013; European Commission in Reypens, Lievens and Blazevic, 2019). In our study, we showed the transition between two types of orchestrators (i.e.…”
mentioning
confidence: 52%
See 4 more Smart Citations
“…Existing studies on network orchestration focused on one type of orchestrator at a time (e.g. UK government organization in Paquin and Howard-Grenville, 2013; European Commission in Reypens, Lievens and Blazevic, 2019). In our study, we showed the transition between two types of orchestrators (i.e.…”
mentioning
confidence: 52%
“…In addition, orchestrators can choose between different orchestration modes to govern relationships in the network, namely, a consensus-based mode with shared participant governance, a dominating mode with highly centralized governance, or a hybrid mode as a combination of both (Davis and Eisenhardt, 2011;Möller and Rajiala, 2007;Reypens, Lievens and Blazevic, 2019). Lead organizations in the networks (i.e.…”
Section: Network Orchestration Researchmentioning
confidence: 99%
See 3 more Smart Citations